Factors associated with delayed enteral nutrition in the intensive care unit: a propensity score–matched retrospective cohort study. Issue 1 (7th April 2021) - Rupert, Amanda A; Seres, David S; Li, Jianhua; Faye, Adam S; Jin, Zhezhen; Freedberg, Daniel E
ABSTRACT: Background: Guidelines recommend enteral nutrition (EN) within 48 h of admission to the medical intensive care unit (ICU) in appropriate patients. However, delayed EN is still common. Objectives: This study sought to identify risk factors for delayed EN ordering in the ICU and to examine its association with patient outcomes. Methods: This was a retrospective study from 2010–2018. Adult patients were included if they were admitted to the medical ICU for >48 h, were appropriate for EN, and had an order for EN placed within 30 d of admission. The primary outcome was ordering of EN, classified as early if ordered within 48 h of ICU admission and otherwise as delayed. Propensity score matching was used to examine the relation between delayed EN and ICU-free days, and outcomes such as length of ICU admission, length of hospitalization during 30 d of follow-up, and mortality. Results: A total of 738 (79%) patients received early EN and 196 (21%) received delayed EN. The exposures most strongly associated with delayed EN were order placement by a Doctor of Medicine compared with a dietitian [adjusted OR (aOR): 2.58; 95% CI: 1.57, 4.24] and use of vasopressors within 48 h of ICU admission (aOR: 1.78; 95% CI: 1.22, 2.59). After propensity score matching to balance baseline characteristics, delayed EN ordering was significantly associated with fewer ICU-free days, longer ICU admissions, and longer hospitalizations, but not mortality, compared with early EN. Conclusions: Provider-level factors were associated with delayed ordering of EN which itself was associated with worse outcomes. Interventions directed at providers may increase timely EN in the ICU and improve outcomes.